Extension-Led Demonstration: Grameen Microfinance Methods and Capital Access for Low-Income Female Entrepreneurs - Mark A. Edelman ([TEST] Journal of Extension, 2021)
A nonprofit community development financial institution and Extension collaborated to conduct a demonstration project to evaluate efficacy of Grameen peer-group microfinance methodology in addressing barriers faced by low-income women entrepreneurs in a small metro area. Program performance metrics achieved by 284 culturally diverse, low-income entrepreneurs (almost all women) over 5 years included a program loan repayment rate of 99%, increased average client income, bank savings accumulation, and increased opportunities for improved credit scores. Client survey responses indicated program methods developed confidence and skills in finances, leadership, and teamwork. Extension professionals may play various roles in such endeavors.
Keywords: microfinance; microenterprise; poverty reduction; cultural diversity; financial literacy